Los dientes no son para morder= Teeth are not for biting - Verdick, Elizabeth; Heinlen, Marieka; Rojas, Edgar (Translator); Verdick, Elizabeth; Verdick, Elizabeth (Minneapolis, MN : Free Spirit Publishing Inc., 2017)
Simple text and illustrations demonstrate what teeth are supposed to be used for instead of biting.
Cover title.
On board pages.
Ages 0-3.
In English and Spanish.
Keywords: Toddlers -- Juvenile literature; Teeth -- Juvenile literature; Dentition -- Juvenile literature; P?rvulos -- Novela juvenil; Dientes -- Novela juvenil; Dentici?n -- Novela juvenil; Board books